Ecosystem Services Dynamics in Bogor Regency - Hariadi Kartodihardjo; Muhammad Buce Saleh; Nurwadjedi Nurwadjedi; Sri Lestari Munajati (Indonesian Journal of Geography, 2021)
The decline in the quality of ecosystem services in Bogor Regency is indicated by the existence of various natural disasters in recent years. Prudent development must be carried out to minimize the impact of a decrease in the ecosystem services index. The purpose of this research is to map ecosystem services for food supply, water supply, water and flood management, and tourism aspects within 2000-2017. The data used were land cover and land facet maps at a scale of 1:25,000 obtained from BIG, accompanied by a reinterpretation process. The data sources were Indonesia's topographic maps (RBI), Citra SPOT 7, DEMNAS, and field surveys. The ecosystem services index (ESI) is calculated based on an analysis of changes in land use and land facets. The value of ESI was weighted using analytic hierarchy process approaches to each of the variables assessed by experts. The results showed that the largest changes in land use occurred in residential and forest areas. The residential area increased by 1.96%, while the forest area decreased by 1.8% in 17 years. Bogor Regency is dominated by forest and rice fields which are spread over four main landforms, namely volcanic, structural, fluvial, and karst. The most significant increase of 5.65% was found in the clean water provisioning function, while the most significant decrease of 38.47% was found in the tourism and ecotourism sector. Accumulatively, the increase in ESI was 23%, while the decrease was 20.64%.  Mitigation efforts that can be done are to maintain the availability of green open space by implementing strong regulations.